PECULARITIES OF METABOLIC DISORDERS IN HYPOTHA-LAMIC SYNDROME PUBERTAL PERIOD IN CHILDHOOD AND ADOLESCENCE - Khyzhnyak, O.O. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
Studying the course of lipid metabolism in teen-age boys with pubertal period hypothalamic syndrome (PPHS) makes it possible to establish three types of dyslipoproteidemia (DLP): II-a, IV and hypoalphaholesterinemia. There is statistical significance between obesity, PPHS сlinical forms and DLP. The patients with PPHS and type IV obesity have high risk of atherosclerosis development.